2013
DOI: 10.1007/s00464-013-3034-0
|View full text |Cite
|
Sign up to set email alerts
|

Does laparoscopic adrenalectomy jeopardize oncologic outcomes for patients with adrenocortical carcinoma?

Abstract: Despite typically being performed in patients with smaller tumors, laparoscopic adrenalectomy for ACC is associated with higher rates of recurrence, particularly peritoneal recurrence. For patients with known or suspected ACC, the oncologic benefits of open resection outweigh the short-term benefits of minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 23 publications
4
87
3
5
Order By: Relevance
“…Nine cohort studies on the surgical treatment of patients with nonmetastatic adrenocortical carcinoma were included (151,152,153,154,155,156,157,158,159). Three studies reported on the patients in whom complete resection of the tumor was achieved (153,155,159).…”
Section: Surgical Approach: Open Vs Minimally Invasive Adrenalectomy mentioning
confidence: 99%
“…Nine cohort studies on the surgical treatment of patients with nonmetastatic adrenocortical carcinoma were included (151,152,153,154,155,156,157,158,159). Three studies reported on the patients in whom complete resection of the tumor was achieved (153,155,159).…”
Section: Surgical Approach: Open Vs Minimally Invasive Adrenalectomy mentioning
confidence: 99%
“…B. Cooper и соавт. предпочтение отдается открытой хирургии, так как данный вид доступа увеличивает безрецидивную вы-живаемость в группе открытых оперативных вмеша-тельств по сравнению с лапароскопической хирургией [23,24].…”
Section: Discussionunclassified
“…In this case, the open approach facilitated complete mobilization of the liver and vena cava with an en bloc resection of the tumor with surrounding soft tissues and no violation of the capsule. This technique limits the possibility of peritoneal seeding, which is more frequently observed after minimally invasive adrenalectomies (5).…”
Section: Case Reportmentioning
confidence: 99%